Increasing the role of husbands in supporting the mental health of pregnant women in the third trimester through childbirth preparation education - Yoga Tri Wijayanti; Ummul Khair; Gustini Gustini (Jurnal Pengabdian Masyarakat Edukasi Indonesia, 2025)
Pregnancy, particularly in the third trimester, is a critical phase where women often experience increased anxiety, stress, and emotional changes due to physical discomfort and anticipation of childbirth. The role of husbands as primary companions during this stage is essential to provide psychological support and strengthen maternal mental health. This community service program aimed to increase husbands’ involvement in supporting their wives through structured childbirth preparation education. The program was conducted using participatory methods, including counselling sessions, interactive discussions, and practical demonstrations that involved both pregnant women and their husbands. Educational materials covered topics such as recognising emotional changes, stress management, effective communication, relaxation techniques, and preparation for public speaking. The results showed that husbands who participated in the program demonstrated improved understanding of maternal needs, enhanced empathy, and greater readiness to provide emotional and physical support. Pregnant women reported feeling more secure, valued, and less anxious when their husbands actively engaged in the preparation process. This initiative highlights the importance of involving partners not only in physical readiness for childbirth but also in strengthening mental resilience. In conclusion, childbirth preparation education for husbands is an effective strategy to foster supportive family environments, reduce maternal stress, and promote healthier maternal mental well-being during the third trimester of pregnancy. This approach is recommended as a sustainable community-based intervention to improve maternal health outcomes.